Three birds with one stone: a single AIEgen for dual-organelle imaging, cell viability evaluation and photodynamic cancer cell ablation. (4th January 2022) - Zhang, Yuewei; Wang, Shuohang; Zhang, Ning; Wang, Xiaodong; Zan, Qi; Fan, Li; Yu, Xue; Shuang, Shaomin; Dong, Chuan
Abstract : We report the first single AIEgen that has great potential for dual-imaging of mitochondria/LDs, detection of cell viability and simultaneously photodynamic ablation of cancer cells. Abstract : Fully understanding the relationship among various organelles and cell viability is greatly important to clarify the mechanism of cancer diagnosis and treatment. However, the development of a single fluorescent probe capable of visualizing dual-organelles, cell viability and photodynamic therapy (PDT) of cancer cells is severely deficient. Herein, we rationally designed and presented a multifunctional aggregation-induced emission luminogen (AIEgen), Mito-TTPE, which first localized in mitochondria with near-infrared (NIR) fluorescence, and further was partially hydrolyzed by esterase, resulting in the accumulation of lipophilic and blue-emissive LD-TTP in lipid droplets. Owing to the distinct two-color emission and dual-organelle targeting changes tuned by esterase hydrolysis, Mito-TTPE was successfully used for evaluating cell viability. More importantly, the remarkable ROS generation ability of Mito-TTPE enabled the efficient photodynamic ablation of cancer cells.